(untitled) (Global Journal of Medical Research, 2023)
The present investigation is to prepare and evaluate transfersomal Nebivolol hydrochloride transdermal patches Rotary evaporation process was used to prepare the nanocarriers Soya lecithin when used in conjunction with Labrosol was proven to be an effective edge activator for the manufacture of Nebivolol hydrochloride nanocarriers Several characteristics of the produced nanocarriers were measured including size entrapment efficiency Zeta potential and photodynamic interference A design expert programme called DOE central composite design was used to optimise the formulations that were chosen The improved formulation 40 w v Labrosol and 68 w v soya lecithin exhibited particle sizes of 1434 5nm Zeta value of -39 8 and a percent Entrapment effectiveness of 96 percent among other characteristics